Speech Acts in US Presidential Candidates' Speeches - Kroupa, Jan (Univerzita Pardubice, 2017)
This paper deals with speech acts in the political speeches and debates of two US presidential candidates. The theoretical part focuses on speech acts, mainly on the illocutionary act and its classification using the description and comparison of two taxonomies. The goal of the analytical part is to find out which illocutionary acts and forces are the most common in the corpus. In the practical part, the use of politeness strategies connected with the application of various speech acts will be discussed, too.
Řečové akty v projevech prezidentských kandidátů USA
Keywords: speech acts; illocutionary force; political speeches; perlocutionary effect; řečové akty; ilokuční síla; politické projevy; perlokuční efekt